2022
DOI: 10.1155/2022/1856075
|View full text |Cite|
|
Sign up to set email alerts
|

[Retracted] Risk Factors Affecting the Infusion Rate of Chemotherapeutic Agents within 2 Hours after Preparation and the Intervention Effect of the Quality Control Circle

Abstract: Objective. To investigate the risk factors for the infusion rate of chemotherapeutic agents within 2 hours after preparation and to observe the application effect of the quality control circle. Methods. The infusion rates of chemotherapeutic agents within 2 hours after the preparation in different wards of our hospital in February 2019 were counted and relevant factors were collected. Binary logistic regression analysis was utilized to screen the risk factors for the infusion rate of chemotherapeutic agents wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…This article has been retracted by Hindawi following an investigation undertaken by the publisher [ 1 ]. This investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process: Discrepancies in scope Discrepancies in the description of the research reported Discrepancies between the availability of data and the research described Inappropriate citations Incoherent, meaningless and/or irrelevant content included in the article Peer-review manipulation …”
mentioning
confidence: 99%
See 1 more Smart Citation
“…This article has been retracted by Hindawi following an investigation undertaken by the publisher [ 1 ]. This investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process: Discrepancies in scope Discrepancies in the description of the research reported Discrepancies between the availability of data and the research described Inappropriate citations Incoherent, meaningless and/or irrelevant content included in the article Peer-review manipulation …”
mentioning
confidence: 99%
“…Tis article has been retracted by Hindawi following an investigation undertaken by the publisher [1]. Tis investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process:…”
mentioning
confidence: 99%